Inositol Improves Cold Tolerance Through Inhibiting CBL1 and Increasing Ca2+ Influx in Rapeseed (Brassica napus L.) - Yan, Lei; Zeng, Liu; Raza, Ali; Lv, Yan; Ding, Xiaoyu; Cheng, Yong; Zou, Xiling (Frontiers in Plant Science, 2022)
Cold stress is an abiotic factor affecting plant growth and crop productivity. The calcium channel is regarded as key pathways affecting cold tolerance. Rapeseed (Brassica napus L.) is an important oil crop worldwide and susceptible to freezing damage. Cold stress affects the planting area and yield of rapeseed. Improving cold tolerance of rapeseed is of great significance. Here, inositol, a cyclic polyol, positively regulated cold tolerance by increasing Ca2+ influx in rapeseed (Brassica napus L.). Furthermore, we found that CBL1 (calcineurin B-like) inhibited by inositol and mediating Ca2+ flux under cols stress, played key role in inositol-Ca2+ cold tolerance pathway. It is worth mentioning that, due to its high safety and low price, inositol can be sprayed on crops in field production. Our study provides new insights into plant cold tolerance mechanism, and introduces a feasible method to improve the cold tolerance of crops quickly.